TEACHING AND LEARNING ENGLISH LINGUISTICS AT UNDERGRADUATE LEVEL AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES - VIETNAM NATIONAL UNIVERSITY, HANOI: CHANGES OVER THE LAST TEN YEARS - Tam, Nguyen Thi Minh (VNU Journal of Foreign Studies; Vol 34 No 5, 2018)
This paper, which is not a research paper, elaborates on the innovations made in English linguistics undergraduate courses at the University of Languages and International Studies - Vietnam National University, Hanoi (ULIS) during the last ten years, from 2009 to 2018. The report on the changes in teaching and learning English linguistics was informed from the 4 published research papers, the contents of which functioned as jigsaw pieces together combining and complementing to make up the complete picture of teaching and learning English linguistics at ULIS over the last decade. The report was also informed from the observation of how English linguistics has been taught and learnt over the last ten years by the author in the roles of a teacher of English linguistics and a course developer at ULIS as well. The comparison between the scenarios of English linguistics teaching and learning before and after 2014 was made, from which the outstanding innovations in teaching and learning English linguistics over the last decade could be seen.